Studies on maintaining seed longevity and the effect of fruit grades in Neem (Azadirachta indica) - Ponnuswamy, A.S. (2023)
Grading of neem (Azadirachta indica) depulped fruits by the floatation method gave 18% floaters. These weighed comparatively less than the sinkers, possessed a higher endocarp content and recorded low viability in terms of maximum germinability and also vigour. The sinkers in contrast recorded an increase of 35% in viability and 92% in vigour index. In a separate study, seeds stored at an ambient temperature of 33.8" C recorded a germinability of 8% at the end of three months compared to 90% when freshly collected. This is attributed to desiccation injury as the moisture content dropped from an initial 30.8 to a low 15.5% at the end of three months. In contrast, seeds stored in earthern pots buried in moist sand bed manifested little loss in seed moisture content and recorded a germinability of 62% at the end of three months. Density grading for maximising viability and vigour and moist storage in earthern pots for prolonging longevity is recommended for the species.